2021
DOI: 10.1108/scm-03-2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain in the C-suite: the effect of chief supply chain officers on incidence of product recalls

Abstract: Purpose This study aims to investigate the extent to which the presence of chief supply chain officers (CSCOs) in top management teams (TMTs) helps firms to reduce the incidence of product recalls. Design/methodology/approach The authors identified all recalls for the period 2010–2017 issued by publicly held firms regulated by the US Consumer Product Safety Commission. These data were subsequently combined with information on TMT composition from BoardEx and financial performance data from Compustat to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 118 publications
0
4
0
1
Order By: Relevance
“…Firms can send a strong signal to the market that they are serious about improving quality by creating SCOM roles on the TMT and hiring SCOM-experienced CEOs. We also join the growing literature indicating that SCOM representation on the TMT is an important driver of organizational strategy and has real world implications to quality and other outcomes (Körber & Cotta, 2021;Kumar et al, 2020;Kumar & Paraskevas, 2018).…”
Section: Managerial Implicationsmentioning
confidence: 75%
See 2 more Smart Citations
“…Firms can send a strong signal to the market that they are serious about improving quality by creating SCOM roles on the TMT and hiring SCOM-experienced CEOs. We also join the growing literature indicating that SCOM representation on the TMT is an important driver of organizational strategy and has real world implications to quality and other outcomes (Körber & Cotta, 2021;Kumar et al, 2020;Kumar & Paraskevas, 2018).…”
Section: Managerial Implicationsmentioning
confidence: 75%
“…However, the manner in which SCOM representation in the TMT might affect firm‐level supply chain outcomes has not been well studied. This study adds to the growing stream of literature exploring the presence of SCOM representation among top executives (Hendricks et al, 2014; Körber & Cotta, 2021; Kumar et al, 2020; Kumar & Paraskevas, 2018; Roh et al, 2016; Wagner & Kemmerling, 2014) by investigating the effects of their presence on product recalls.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Por otro lado, Melville, Kraemer y Gurbaxani [25] explicaron que las TI conectan las diferentes empresas a través de la fusión de negocios y la búsqueda ágil de proveedores y clientes [7]. Por lo tanto, dentro del contexto del desarrollo e implementación de las TI, es necesario incluir al recurso humano tanto de la coordinación de actividades internas como de la organización externa a la empresa [22], [31].…”
Section: Enunclassified
“…On the other hand, Melville et al [14] explained that IT connects different companies through business mergers and the agile search for suppliers and customers [15]. Therefore, within the context of the development and implementation of IT, it is necessary to include human resources both for the coordination of internal activities and for the organization external to the company [16]. Finally, Ghobakhloo et al [13] revealed that the implementation and application of IT is a major driver behind many socioeconomic changes.…”
Section: Introductionmentioning
confidence: 99%